(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2023)
This study was aimed to determine the characteristics of the soils of perennial ryegrass genotypes found in the natural flora in the Central Anadolu Region in Türkiye. Within the scope of the study, perennial ryegrass populations were collected from the provinces of Ankara, Eskişehir, Afyon, Konya, Aksaray, Karaman and Mersin and Antalya provinces in 2006 and 2007. Plants were collected and soil samples were taken and analysed from 87 sites in Ankara (20), Eskişehir (9), Afyon (5), Konya (39), Aksaray (1), Karaman (5), Mersin (2) and Antalya (6). According to the analysis results, the pH varied between 6.35-8.50, EC 52-1395 µS/cm, organic matter 0.04-9.1 %, lime 1.2-64.2%, P2O5 4.28-128.7 mg/kg, K2O 24.7-1360. 8 mg/kg, Ca 820-4030 mg/kg, Mg 32.7-3569 mg/kg, Na 0.6-2016 mg/kg, Fe 2.78-67.50 mg/kg, Zn 0.10-8.97 mg/kg, Cu 0.21-9.43 and Mn 2.33-42.34 mg/kg. As a result of soil analyses, large differences were observed between the locations where plants were collected in terms of the characteristics examined. This change shows the potential of developing grass varieties that can grow in different soil properties with a good breeding study of perennial ryegrass populations.